2018
DOI: 10.3390/atmos9120472
|View full text |Cite
|
Sign up to set email alerts
|

Extreme Rainfall and Flooding over Central Kenya Including Nairobi City during the Long-Rains Season 2018: Causes, Predictability, and Potential for Early Warning and Actions

Abstract: The Long-Rains wet season of March-May (MAM) over Kenya in 2018 was one of the wettest on record. This paper examines the nature, causes, impacts, and predictability of the rainfall events, and considers the implications for flood risk management. The exceptionally high monthly rainfall totals in March and April resulted from several multi-day heavy rainfall episodes, rather than from distinct extreme daily events. Three intra-seasonal rainfall events in particular resulted in extensive flooding with the loss … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
72
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 78 publications
(85 citation statements)
references
References 27 publications
8
72
0
Order By: Relevance
“…Kilavi et al . () report that “Over the Kenya‐core region and indeed Kenya as a whole, 2018 saw the wettest MAM season over the 119‐year record of the Global Precipitation Climatology Centre (GPCC) data, and the 118 years of Centennial Trends (CenTrends) data.”. Their figure c shows that this was in fact the case for the majority of the Lake Victoria Basin.…”
Section: Case‐study Of 2018 Long Rainssupporting
confidence: 79%
See 4 more Smart Citations
“…Kilavi et al . () report that “Over the Kenya‐core region and indeed Kenya as a whole, 2018 saw the wettest MAM season over the 119‐year record of the Global Precipitation Climatology Centre (GPCC) data, and the 118 years of Centennial Trends (CenTrends) data.”. Their figure c shows that this was in fact the case for the majority of the Lake Victoria Basin.…”
Section: Case‐study Of 2018 Long Rainssupporting
confidence: 79%
“…Kilavi et al . () have also shown that both these datasets perform well over Kenya during this period compared to gauge station measurements. The three periods where rain rates are anomalous compared to the climatology are: days 0–5 (P1), days 14–19 (P2), and days 43–54 (P3).…”
Section: Case‐study Of 2018 Long Rainsmentioning
confidence: 90%
See 3 more Smart Citations